Relationships Between School Characteristics And Character Building of Pupils in Chinese Primary Schools in Malaysia - Ho, Nee Yong (2013)
The main research question for this study is: To what extent do school characteristics contribute to the character building of pupils in Chinese primary schools in Malaysia? The operational deﬁnitions of ‘characteristics’ in this study are the eight independent variables namely: 1) Dong Jia Jiao (DJ J E5550, an abbreviation of School Boards of Governors and Parent-Teacher Associations, 2) Mother tongue education, 3) Trilingualism, 4) Confucianism, 5) School discipline, 6) Teachers, 7) Pedagogy, and 8) Environment _- home and school. These eight variables were condensed into six based on Conﬁrmatory Factor Analysis. The sole dependent variable is Character building of which the operational deﬁnition encompasses the eagerness to study, practising good values and having a sense of shame. (Chen, 1966) A total of 554 sets of questionnaires were sent to 45 Chinese primary schools in 14 states in Malaysia, and 508 sets (91.7%) were returned. The different tests used in this study included factor analysis, t-test, Analysis of Variance (ANOVA), Chi-square test, and Multiple Linear Regression. The triangulation approach was adopted to triangulate the quantitative data from the questionnaires derived from literature review, with the qualitative data obtained from the interviews. The ﬁnal analysis of data showed that school characteristics contributed 36.8% to the character building of Chinese primary school pupils as follows: Teachers and pedagogy (24.3%), Environment (6.6%), Mother tongue education (3.1%), DJJ (1.2%), Confucianism and school discipline (1.0%), and Trilingualism (0.6%). The balance of 63.2% therefore comes from other extemal factors which affect the character building of pupils. Recommendations have been offered to Chinese primary schools for the further enhancement of character building of pupils. The future research study on developing educational innovations towards character building, better national integration and racial harmony in Malaysia will be a vital research to pursue. From the insightful mentors of China from the East to the distinguished educators of the West come the teachings and practices of education which vary as greatly as the expanse between these continents. Their goal, however, is united: to spawn educated individuals with wholesome personalities. Their goal is plain and noble: for a better and more virtuous future generation through an all-round education. This study therefore aims to provide a harmony of learning to children and to nurture them with a versatile form of teaching. As the paths to a better and full education converge, so will the objectives of a sound knowledge, namely for children to be achievers in their careers while retaining their morals.